Emotional Intelligence and School Environment as the Predictors of Achievement in Science of Ninth Standard Students - Gangwar, Sumit (SCHOOL SCIENCE, 2025)
The main objective of the present research work is to study the contribution of emotional intelligence and the school environment in predicting the achievement in science of IX standard students. Descriptive survey method was used in this study. As a sample, the researcher selected a school among the secondary level schools affiliated to the Board of High School and Intermediate Education, Prayagraj (Uttar Pradesh) in Pilibhit district by purposive sampling technique and 50 students of Class IX studying in this school were included in the final sample with the help of accidental sampling technique. A self-made-standardised Science Achievement Test was used to measure achievement in science, an Emotional Intelligence Inventory developed and standardised by S.K. Mangal and Shubhra Mangal was used to assess the Emotional Intelligence and a School Environment Inventory developed and standardised by K.S. Misra was used for measuring School Environment. Regression analysis of statistical technique was used to analyse the collected data. As a result of the research, it was found that the emotional intelligence of students studying in Class IX does not contribute to predicting achievement in science, whereas the school environment makes a significant contribution to predict achievement in science of IX standard students.